Qualitative and Quantitative Loss of Habitat at Different Spatial Scales Affects Functional Moth Diversity - Uhl, Britta; Wölfling, Mirko; Fiedler, Konrad (Frontiers in Ecology and Evolution, 2021)
Land use change has led to large-scale insect decline, threatening ecosystem resilience through reduced functional diversity. Even in nature reserves, losses in insect diversity have been detected. Hereby, changes in local habitat quality and landscape-scale habitat quantity can play a role driving functional diversity erosion. Our aim was to analyze how local and landscape-scale factors simultaneously affect functional insect diversity. Therefore, we sampled moths in two Italian coastal forest reserves at 60 sites. Our focus was on functional richness, redundancy and niche occupation, being important for ecosystem resilience, following the insurance-framework. Ecological information of 387 species and 14 traits was used to analyze functional diversity. Twenty-five functional groups were recognized and used to estimate niche occupation and redundancy. Fourteen local and 12 landscape-scale factors were measured and condensed by using Principal Components Analysis. The resulting PC-axes served as predictors in linear mixed effects models. Functional richness, redundancy and niche occupation of moths were lower at sites with low habitat quality and quantity, indicating reduced ecosystem resilience. Especially landscape diversity and habitat structure, viz. a humidity-nutrient gradient, but also plant diversity, were promoting functional richness. Landscape fragmentation, indicating increased impermeability for insects, reduced local functional richness, redundancy and niche occupation. Local habitat quality and landscape-wide habitat quantity are both important for maintaining functional insect diversity inside reserves. Therefore, small and isolated nature reserves might fail in preserving biodiversity and ecosystem functions through adverse effects acting from the surrounding landscape structure and configuration.